Nan-Ching : The Classic of Difficult Issues. - Unschuld, Paul U. (Comparative Studies of Health Systems and Medical Care Series., 2022)
Although the study of traditional Chinese medicine has attracted unprecedented attention in recent years, Western knowledge of it has been limited because, until now, not a single Chinese classical medical text has been available in a serious philological translation. The present book offers, for the first time in any Western language, a complete translation of an ancient Chinese medical classic, the Nan-ching. The translation adheres to rigid sinologic.